[PAL pilot ; Guian ; Burger Wars [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
The making of a PAL pilot, aviation school and the rigors of making the grade. Looks at the disaster relief operations in a town in Western Samar that is periodically ravaged by typhoons.
PAL pilot (20 min.) -- Guian (18 min.) -- Burger wars (14 min.)
VHS.
Keywords: Philippine Air Lines; Airline Pilots Association of the Philippines; Air pilots -- Philippines; Disaster victims -- Philippines -- Samar; Fast food restaurants -- Marketing -- Philippines; Typhoons -- Philippines -- Samar